2009
DOI: 10.1088/0951-7715/22/6/r01
|View full text |Cite
|
Sign up to set email alerts
|

Semiclassical analysis and passive imaging

Abstract: The propagation of elastic waves inside the Earth provides us with informations about the geological structure of the Earth's interior. Since the beginning of seismology, people have been using waves created by earthquakes or by artificial explosions. They record the waves as functions of time using seismometers located at different stations on the Earth's surface. Even without any earthquake or explosion, a weak signal is still recorded which has no evident structure: it is a "noise". How to use these noises?… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
56
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 35 publications
(70 reference statements)
0
56
0
1
Order By: Relevance
“…In the case of a spatially localized distribution of noise sources, directional diversity of the recorded fields can be enhanced if there is sufficient scattering in the medium. An ergodic cavity with a homogeneous interior is a good example ( Figure 2.4, left): Even with a source distribution that has very limited spatial support, the reverberations of the waves in the cavity generate interior fields with high directional diversity [15,2]. Multiple scattering of waves by random inhomogeneities can also lead to wave field equipartition if the transport mean free path is short compared to the distance from the sources to the sensors [30,21,27].…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of a spatially localized distribution of noise sources, directional diversity of the recorded fields can be enhanced if there is sufficient scattering in the medium. An ergodic cavity with a homogeneous interior is a good example ( Figure 2.4, left): Even with a source distribution that has very limited spatial support, the reverberations of the waves in the cavity generate interior fields with high directional diversity [15,2]. Multiple scattering of waves by random inhomogeneities can also lead to wave field equipartition if the transport mean free path is short compared to the distance from the sources to the sensors [30,21,27].…”
Section: 2mentioning
confidence: 99%
“…When the support of the random noise sources extends over all space and they are uncorrelated, that is, their spatial correlation is a delta function, it has been shown that the derivative of the cross correlation of the recorded signals is the symmetrized Green's function between the sensors [26]. This is also true with spatially localized noise source distributions provided the waves propagate within an ergodic cavity [15,16,2]. At the physical level this result can be obtained in both open and closed environments provided that the recorded signals are equipartitioned [22,37,25,33,23].…”
mentioning
confidence: 96%
“…[10,19], provided that the noise sources surround the region of interest. In the case of closed systems, i.e., cavities, the sources can be spatially localized provided the cavity is ergodic [1,6]. The first application of these ideas to imaging was in helioseismology [7] and, more recently, in passive seismic imaging of the surface velocity of the earth [13,15].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the Green's function of the wave equation in an inhomogeneous medium can be estimated by cross correlating the signals emitted by ambient noise sources and recorded by a passive sensor array [7,17,18]. The idea has been used for travel time estimation and background velocity estimation in geophysical contexts, and also for passive sensor imaging of reflectors [9,10], which consists of backpropagating or migrating the cross correlation matrix of the recorded signals.…”
mentioning
confidence: 99%